Equilibrium real interest rates and secular stagnation: An empirical analysis for euro area member countries - Ansgar Belke; Jens Klose (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
Is secular stagnation a valid concern for Euro Area countries? We tackle this question using the well-established Laubach-Williams model to estimate the unobservable equilibrium real interest rate and compare it to the actual real rate. We apply our approach to twelve Euro Area countries, since heterogeneity among member countries has become considerably extensive since the beginning of the financial crisis. Hence, the question of secular stagnation has to be answered at the country level. Our results indicate that secular stagnation does not appear to be a significant threat to most Euro Area countries. But there is one exception: Greece. – – Ist säkulare Stagnation ein Problem in den Ländern des Euro Raums? Wir widmen uns dieser Frage, indem wir das etablierte Modell von Laubach und Williams (2003) anwenden, um den unbeobachtbaren gleichgewichtigen Realzins zu schätzen und mit dem tatsächlichen Realzins zu vergleichen. Der Ansatz wird für zwölf Länder des Euro Raums angewendet, weil die Heterogenität zwischen den Mitgliedstaaten seit Ausbruch der Finanzkrise erheblich zugenommen hat. Deshalb muss die Frage der säkularen Stagnation auf Länderebene beantwortet werden. Die Ergebnisse zeigen, dass säkulare Stagnation für die meisten Staaten der Währungsunion keine signifikante Bedrohung darstellt. Aber es gibt eine Ausnahme: Griechenland.
Keywords: E43; F45; C32; 330; equilibrium real interest rate; secular stagnation; Euro Area countries; heterogeneity